2022-RA-1315-ESGO Anti-LSR monoclonal antibody exerts an antitumor activity associated with apoptosis in endometrial cancer. (20th October 2022) - Nagase, Yoshikazu; Hiramatsu, Kosuke; Kakuda, Mamoru; Nakagawa, Satoshi; Kobayashi, Eiji; Kimura, Toshihiro; Serada, Satoshi; Ueda, Yutaka; Naka, Tetsuji; Kimura, Tadashi
Abstract : Introduction/Background: Advanced endometrial cancer (EC) remains a disease with a poor prognosis. Since the efficacy of current chemotherapy is limited, new therapeutic agents are need to be investigated. We focused on lipolysis-stimulated lipoprotein receptor (LSR), a membrane protein highly expressed in EC cells, and developed a novel chimeric chicken-mouse anti-LSR monoclonal antibody (mAb). The aim of this study was to investigate the function of LSR and the antitumor activity of anti-LSR mAb in EC. Methodology: The relationship between LSR expression level and clinical outcomes was investigated using immunohistochemistry in 230 clinical samples of EC. To clarify the function of LSR, we conducted in vitro assays using LSR-knockdown EC cell lines (HEC1 and HEC116) generated by transfected with siRNA. We investigated the antitumor activity of anti-LSR mAb in EC cell xenograft mouse model. Results: Patients were divided into two groups based on LSR expression level; High-LSR (n=153) and Low-LSR (n=75) groups. The 5-year overall survival rate in High-LSR group was significantly lower than that in Low-LSR group (hazard ratio: 3.53, 95% confidence interval: 1.35–9.24, p=0.01). In addition, High-LSR expression was associated with deep myometrial invasion and distant metastasis in EC (p < 0.05, respectively). In vitro analysis demonstrated that LSR-knockdown suppressed the activation of MEK/ERK signaling and subsequent matrix metalloproteinases (MT1-MMP and MMP2), which downregulated cell proliferation, invasion, and migration. Our anti-LSR mAb significantly inhibited the tumor growth in EC cell xenograft mouse model (p = 0.019). Anti-LSR mAb suppressed the activation of ERK1/2 and increased the expression of cleaved caspase-3 in vivo. Moreover, anti-LSR mAb also suppressed the activation of MEK/ERK signaling in vitro. Conclusion: LSR is associated with tumor growth, invasion, metastasis, and poor prognosis through MAPK signaling in EC. Anti-LSR mAb is a potential therapeutic agent which induces apoptosis and shows a significant antitumor effect in EC.